2006
DOI: 10.2460/javma.228.2.225
|View full text |Cite
|
Sign up to set email alerts
|

Effects of diet on clinical signs of exocrine pancreatic insufficiency in dogs

Abstract: Results indicated that responses to different diets varied among individual dogs. Because responses to the feeding regimens were unpredictable, it is suggested that feeding regimens be individually formulated for dogs with EPI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 17 publications
0
4
0
3
Order By: Relevance
“…Dietary management is recommended as adjunctive therapy in canine EPI, and the most important consideration appears to be in fat content with fat restriction recommended in some [10,11], but not all [12,13], studies. Further, prospective studies have not demonstrated a clear benefit of any specific diet in the treatment of canine EPI [13-15]. In fact, different diet types (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary management is recommended as adjunctive therapy in canine EPI, and the most important consideration appears to be in fat content with fat restriction recommended in some [10,11], but not all [12,13], studies. Further, prospective studies have not demonstrated a clear benefit of any specific diet in the treatment of canine EPI [13-15]. In fact, different diet types (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The small intestinal microbiota, even if of normal composition, can contribute to clinical signs when there is an abnormal or increased amount of food or drug substrate in the intestinal lumen. This can be due to feeding diets with poor digestibility, inflammatory diseases that damage the transporters in the epithelial brush border, 28,29 and a lack of digestive enzymes in patients with exocrine pancreatic insufficiency (EPI) 30 . Therefore, abnormal microbial conversion of luminal substrates by normal microbiota can be pathologic, not just changes in bacterial populations.…”
Section: Assessment Of the Intestinal Microbiome—general Considerationsmentioning
confidence: 99%
“…This can be due to feeding diets with poor digestibility, inflammatory diseases that damage the transporters in the epithelial brush border, 28 , 29 and a lack of digestive enzymes in patients with exocrine pancreatic insufficiency (EPI). 30 Therefore, abnormal microbial conversion of luminal substrates by normal microbiota can be pathologic, not just changes in bacterial populations. While some of the microbiome changes that likely originate in the small intestine can be detected in fecal samples, as reported for dogs receiving omeprazole, 23 , 31 dogs with EPI, 32 and dogs with chronic enteropathies (CE), 33 , 34 the above limitations should nevertheless be considered when analyzing fecal samples only.…”
Section: Assessment Of the Intestinal Microbiome—general Considerationsmentioning
confidence: 99%
“…Studies in the human literature, where cross over design using different pancreatic enzyme supplements for cystic fibrosis have employed 1, 2, or 4 weeks duration. Dietary trials in dogs with EPI have also used a 3 week period, hence we decided to use a 3 week period for each treatment arm in our study.…”
Section: Discussionmentioning
confidence: 99%